Entre gingas e saberes: um estudo sobre a educação das relações étnico-raciais nos cursos de licenciatura da UFG - Paula, Karollina Agatha Schineider de (2024)
This master's thesis examines how the undergraduate programs at the Federal University of Goiás (UFG) have adapted to meet the requirements of Law 10.639/2003. The aim is to understand how subjects related to Education for Ethnic-Racial Relations (ERER), as well as African and Afro-Brazilian history and culture, are taught in various departments and colleges at the university. The theoretical framework focuses on decolonial and anti-racist perspectives, considering the colonial structures and racial issues that shape Brazilian society. This study includes contributions from Black authors. The research involved analyzing documents such as the National Education Guidelines (LDB 9394/96), Law 10.639/2003, along with other educational resolutions and curriculum guidelines. The political-pedagogical projects of UFG's undergraduate courses were also examined, particularly concerning ERER and Afro-Brazilian history. The analysis indicated that while significant progress has been made in establishing affirmative policies, practical implementation remains lacking due to the absence of a requirement for anti-racist courses in the curriculum. Transforming the Brazilian education system into a truly inclusive and anti-racist environment continues to be a major challenge, as the colonial legacy still influences perceptions of Black individuals as inferior, marginalizing their culture and knowledge.